2020
DOI: 10.1002/brb3.1868
|View full text |Cite
|
Sign up to set email alerts
|

White matter abnormalities and cognitive function in euthymic patients with bipolar disorder and major depressive disorder

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 81 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…It should be noted that the brain regions implicated in the current study are also relevant to mood/emotional dysfunction [42,43]. After the introduction of ART in 2005, the relevance of mood dysfunction on HIV-related clinical outcomes focused on the potential negative effects on suboptimal adherence to ART.…”
Section: Discussionmentioning
confidence: 91%
“…It should be noted that the brain regions implicated in the current study are also relevant to mood/emotional dysfunction [42,43]. After the introduction of ART in 2005, the relevance of mood dysfunction on HIV-related clinical outcomes focused on the potential negative effects on suboptimal adherence to ART.…”
Section: Discussionmentioning
confidence: 91%
“…Calcium overload caused by cellular Ca influx under stress has been shown to induce mitochondrial damage, increase ROS generation, and promote K + efflux ( 30 - 32 ), which suggests that mitochondrial damage may be the key to NLRP3 inflammasome activation. Studies have shown that irisin inhibits Ca 2+ influx ( 33 ) and reduces mitochondrial damage ( 34 ), which suggests that aerobic exercise may inhibit the progression of PSD by inhibiting inflammasome activation. We found that aerobic exercise significantly reduced the expression of NLRP3, Caspase1, and IL-1β, which suggests that aerobic exercise plays a key role in inhibiting the activation of the NLRP3 inflammasome, which may be the mechanism underlying the anti-PSD effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studying OABD using DTI methods is a burgeoning area, with several studies showing FA decreases in similar areas as in younger samples with BD, including ventral corpus callosum, and uncinate fasciculus [ 74 , 75 ]. In addition to contributions to emotion dysregulation in BD, contributions to cognitive deficits are implicated by negative correlations between cognitive performance across multiple domains, including working memory, information processing, executive function, and attention, with FA in the corpus callosum and uncinate fasciculus [ 76 78 ]. As cognitive decline is a feature for some individuals with BD during later life, that causes suffering, impaired functioning, and is associated with poor prognosis [ 79 ], elucidating disturbances in these key WM tracts may be integral to preventing some of the severe clinical outcomes associated with BD during later life.…”
Section: White Matter In Bipolar Disordermentioning
confidence: 99%